2022
DOI: 10.33899/ijvs.2022.133212.2190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exogenous oxytocin on the expression of oxytocin receptor gene and uterine involution in local Iraqi cows

Abstract: The present work aimed to study the effect of exogenous oxytocin injection on the expression of the oxytocin receptor gene and the duration of uterine involution in the local Iraqi breed of Karradi cows. Twenty cows were divided into two groups. The first group was considered a control; the second group was injected with 100 IU/IM of oxytocin twice weekly for four weeks postpartum. The uterine involution velocity was monitored using ultrasonography by measuring the endometrium thickness, ovarian diameter, cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2025
2025
2025
2025

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…According to the results of this study that is showed the concentration of the hormones progesterone and estrogen during the last days of pregnancy and in the first stage of labor plays a major role in the process of dilating the cervix and completing parturition in sheep and goats agree with [17]. Al-Watar and Hussein [18] illustrated a significant increment of the estrogen level from the 1 st week to the 4 th week over the postpartum period for all groups. The exogenous oxytocin has also exhibited a significant influence on the E2 concentrations.…”
Section: Discussionsupporting
confidence: 51%
“…According to the results of this study that is showed the concentration of the hormones progesterone and estrogen during the last days of pregnancy and in the first stage of labor plays a major role in the process of dilating the cervix and completing parturition in sheep and goats agree with [17]. Al-Watar and Hussein [18] illustrated a significant increment of the estrogen level from the 1 st week to the 4 th week over the postpartum period for all groups. The exogenous oxytocin has also exhibited a significant influence on the E2 concentrations.…”
Section: Discussionsupporting
confidence: 51%